Description of a new species of Haemaphysalis Koch, 1844 (Acari: Ixodidae), a parasite of hares and rabbits (Lagomorpha: Leporidae) in Texas, Oklahoma and Colorado (USA), that was misidentified as H. leporispalustris (Packard, 1869) for more than a century - Apanaskevich, Dmitry A. (Zootaxa, 2024)
Haemaphysalis (Gonixodes) mariae n. sp. (Acari: Ixodidae) is described based on males and females that were collected from leporids in the United States (Colorado, Oklahoma and Texas). Adults of this new species are similar to those of H. leporispalustris (Packard, 1869), but can be distinguished from them by the punctation pattern of the conscutum and scutum, length of the lateral grooves, length of the lateral salience of palpal segment II, shape of palpal segment III, shape and length of spur on palpal segment III, and on coxa I, as well as by measurements and their ratios.